Udder types and associated traits affect milk composition and subclinical mastitis in Karayaka sheep - AKDAG, FILIZ; TEKE, BULENT; UGURLU, MUSTAFA; ONYAY, FIRDEVS BINLI; KOCAK, OMUR; DEMIR, HIDIR (The Indian Journal of Animal Sciences, 2018)
This study was carried out to determine the relationships between udder type and udder traits and milk composition and subclinical mastitis in Karayaka sheep. For this purpose, udder types were determined and udder and teat traits were measured in 32 Karayaka sheep. In addition, milk fat, protein, lactose, dry matter contents, freezing point, SCC and pH were measured. Our results showed that udder type had an effect on right (RTL) and left (LTL) teat length, right (RTDM) and left (LTDM) teat diameter and teat distance (TD). In addition, udder type was found to have an effect on lactose and pH. High or moderate phenotypic correlations were found between teat traits and lactose, freezing point and pH. In addition, of the phenotypic correlations between udder and teat traits, only the correlation between RTL and SCC was significant. SCC showed high phenotypic correlations with fat, lactose, dry matter, protein, freezing point and pH. Our results showed that udder type was effective on teat size, the sheep whose teats were vertical had low milk lactose and high pH, and the sheep with this type of udder were found to have a higher probability of mastitis.